2020
DOI: 10.1016/j.brs.2020.01.016
|View full text |Cite
|
Sign up to set email alerts
|

The differential roles of contralesional frontoparietal areas in cortical reorganization after stroke

Abstract: Background: Studies examining the contribution of contralesional brain regions to motor recovery after stroke have revealed conflicting results comprising both supporting and disturbing influences. Especially the relevance of contralesional brain regions beyond primary motor cortex (M1) has rarely been studied, particularly concerning the temporal dynamics post-stroke. Methods: We, therefore, used online transcranial magnetic stimulation (TMS) interference to longitudinally assess the role of contralesional (r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
46
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(52 citation statements)
references
References 64 publications
4
46
1
1
Order By: Relevance
“…Though reduced frontoparietal network involvement has been observed in stroke subjects relative to controls, as replicated here, there is evidence that within stroke subjects, increased activity of the frontoparietal network is related to better motor recovery (Tscherpel et al, 2020). Recent work has shown that individuals with CST damage (measured using motor-evoked potentials) have greater resting-state functional connectivity in the frontoparietal network compared to individuals without CST damage (Hordacre et al, 2021a).…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…Though reduced frontoparietal network involvement has been observed in stroke subjects relative to controls, as replicated here, there is evidence that within stroke subjects, increased activity of the frontoparietal network is related to better motor recovery (Tscherpel et al, 2020). Recent work has shown that individuals with CST damage (measured using motor-evoked potentials) have greater resting-state functional connectivity in the frontoparietal network compared to individuals without CST damage (Hordacre et al, 2021a).…”
Section: Discussionsupporting
confidence: 61%
“…In this paper, we aim to identify patterns of activation that are associated with better motor recovery. Recent work has highlighted the importance of frontoparietal areas in supporting motor abilities in the chronic phase of stroke (Tscherpel et al, 2020) specifically in patients with poor corticospinal tract (CST) integrity (Hordacre et al, 2021a). When these descending motor pathways are significantly damaged, descending white matter tracts from higher-order motor areas, such as the premotor cortex, may support motor output.…”
Section: Introductionmentioning
confidence: 99%
“…Similar supportive effects of the contralesional dorsal premotor cortex were also observed in other fMRI and TMS studies [ 4 , 37 ]. Furthermore, a more influential role of the dorsal premotor cortex for hand movements has also been observed in physiological aging [ 69 ], implying a general neural mechanism to support hand motor function. In summary, the roles of contralesional areas in the recovery of motor function post-stroke are region-specific and time-sensitive, which needs to be considered when using non-invasive brain stimulation to improve the functional outcome after stroke.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the VL approach has shown promise in tracking the longitudinal change of the recovery-facilitating role of particular brain regions. A study by Tscherpel and colleagues [54] of patients with first-ever ischemic stroke in the left hemisphere and mild to moderate motor deficit (N=14) found that the time-sensitivity of interference to contralesional frontoparietal areas is region-specific. Another study by the same group [55] found that slow and simple electroencephalogram responses to TMS were associated with both severe motor impairment and poor motor recovery of stroke patients (N=25).…”
Section: Perturbation Probe-based Approachesmentioning
confidence: 99%